KAJIAN PRAGMATIK TINDAK TUTUR DALAM DIALOG NARATIF NOVEL WARISAN DUA DUNIA: PERSPEKTIF AUSTIN DAN SEARLE - Lauli (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2026)
ABSTRACT This study aims to examine speech acts in the narrative dialogues of the novel Warisan Dua Dunia based on the pragmatic perspectives of speech act theories proposed by Austin and Searle. The focus of the research includes the realization of locutionary, illocutionary, and perlocutionary acts, the classification of illocutionary speech acts, and the functions of speech acts within the context of inter-character interactions and plot development. This research employs a descriptive qualitative approach, with data consisting of utterances or dialogues between characters found in the novel Warisan Dua Dunia. Data were collected through reading and note-taking techniques. Data analysis was conducted by identifying speech acts based on Austin’s theory and classifying illocutionary speech acts according to Searle’s framework, followed by an analysis of the functions of utterances in narrative and interactional contexts. The findings indicate that all types of speech acts proposed by Austin, locutionary, illocutionary, and perlocutionary acts, are clearly realized in the dialogues of the novel. Based on Searle’s classification, five types of illocutionary speech acts were identified, namely directive, assertive, expressive, commissive, and declarative acts, with directive and assertive acts being the most dominant. This dominance suggests that the dialogues primarily function as a means of directing characters’ actions and conveying information to clarify narrative situations. Furthermore, speech acts play significant roles as drivers of character activities, builders of social relationships, conveyors of cultural values and traditions, triggers of conflict, and regulators of interaction that contribute to the progression of the storyline. Therefore, the narrative dialogues in Warisan Dua Dunia do not merely serve as communicative tools but function as linguistic actions that actively shape the narrative structure and interactional dynamics among characters. The pragmatic speech act theories of Austin and Searle are proven to be relevant and effective for conducting contextual and in-depth analyses of literary dialogue.